Obywatele i prawo petycji. W stronę zmian? = Citizens and the right of petition. On the way to change? - Post, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article attempts to answer the question of whether the Law on Petitions, adopted in July 2014, which raised hopes for the initiation of civic activity, has actually triggered the expected changes. The analysis of the petitions received by the Polish Sejm since the Act entered into force (September 2015), seems to con?rm these expectations. The way in which the Sejm examines petitions -and it typically adopts decisions to reject them - shows that, regardless of the number of petitions submitted, the e?ectiveness of this legal institution is, by de?nition, limited, as petitions are an instrument of semi-direct democracy. The addressees of petitions are not legally obliged to take their demands into account.
Keywords: prawo petycji; petycja; Sejm; społeczeństwo obywatelskie; right of petition; petition; civil society